Behavioral Finance: Hippocrates Personality and Behavioral of Islamic Finance on Investment Decision Gen Z - Effendi, Kharisya Ayu (Global Review of Islamic Economics and Business, 2023)
This study aims to analyze Hippocrates' personality and an investor's financial behavior in making investment decisions. A quantitative research design was used to test the research hypotheses. The respondents consisted of Muslim students from universities in Bandung who belong to the category of Generation Z. The data analysis technique used was the Structural Equation Model (SEM) AMOS. The Hippocrates personality has a significant effect on financial behavior, and financial behavior has a significant effect on investment decisions. However, the Hippocrates personality does not have a significant effect on investment decisions. The findings of this research indicate that financial behavior needs to be improved by applying Sharia financial concepts so that it can support investment activities that are in line with Sharia principles. Personality Hippocrates emphasized choosing investments that are in line with the student's personality characteristics. This personality type is more inclined towards the behavior of calculating the appropriate risks and benefits of the investments made. The novelty of this research is demonstrated by the Islamic financial perspective which examines the relationship between Hippocrates' personality and financial behavior on investment decision-making. The expected implication is that Islamic finance can increase investment by knowing the Hippocratic personality type and financial behavior among Gen Z Muslims. Originality/Value: The originality of this research is found in studying personality types according to Hippocrates (129-200 BC) and the perspective of Islamic Finance in making investment decisions.